2018
DOI: 10.5588/pha.18.0006
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the effectiveness of smoking cessation interventions among patients with tuberculosis

Abstract: Smoking cessation interventions 38 Public Health Action propion'[Mesh] OR 'Varenicline'[Mesh] OR 'Clonidine'[Mesh] OR 'Nortriptyline'[Mesh] OR 'smoking cessation'[tiab] OR 'smoking cessations'[tiab] OR (('tobacco products'[Mesh] OR 'Tobacco Use'[Mesh] OR 'Smoking'[Mesh] OR 'vaping'[Mesh] OR 'nicotine'[mesh] OR smok*[tiab] OR 'tobacco'[tiab] OR cigar*[tiab] OR e-cig*[tiab] OR 'nicotine'[tiab] OR 'hookah'[tiab] OR 'pipe'[tiab] OR 'vaping'[tiab] OR 'vape'[tiab]) and (quit*[tiab] OR ceas*[tiab] OR cessation*[tiab]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 49 publications
1
22
0
1
Order By: Relevance
“…The World Health Organization [32] and the International Union Against Tuberculosis and Lung Disease provide guidelines [33] for smoking cessation treatment within TB programs. A 2018 systematic review found that interventions provided during TB treatment are feasible and effective in reducing smoking rates among patients [34]. However, considerable variation in treatment components, provider engagement, and time requirements across programs was observed revealing a critical need for further empirical and qualitative research to inform effective integration of cost-effective interventions into standard practice, particularly in low-resource settings.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization [32] and the International Union Against Tuberculosis and Lung Disease provide guidelines [33] for smoking cessation treatment within TB programs. A 2018 systematic review found that interventions provided during TB treatment are feasible and effective in reducing smoking rates among patients [34]. However, considerable variation in treatment components, provider engagement, and time requirements across programs was observed revealing a critical need for further empirical and qualitative research to inform effective integration of cost-effective interventions into standard practice, particularly in low-resource settings.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, smokers were more likely to have UTO than non‐smokers , although we did not find statistically significant differences in our study. However, to improve the overall quality of health of individuals, there is certainly a need to integrate smoking cessation interventions into routine TB services .…”
Section: Discussionmentioning
confidence: 99%
“…There are only two studies that assessed smoking cessation effect at 6 months after completion of anti-TB treatment 23 . To our knowledge, this is the first study to assess long-term changes of smoking status among TB patients.…”
Section: Discussionmentioning
confidence: 99%